Pengaruh Konsentrasi Penyemprotan Auksin Pada Padi (Oryza Sativa) Yang Diberikan Simulasi Cekaman Salinitas - Utama, Yani Putri; Violita, Violita (Universitas Andalas, 2024)
Agriculture is a vital sector in meeting global food needs. The fulfillment of food needs has environmental challenges that cause plants to be exposed to abiotic stress, namely salinity stress. The purpose of this study was to determine the effect of auxin spraying concentration on rice given salt stress. The concentration of auxin sprayed was 25 µm, 37.5 µm, 50 µm, while the concentration of salt given was 0 µm, 15 µm, 30 µm, 45 µm. This research is an experimental research. The research was conducted at the Basic Biology Laboratory, Department of Biology, FMIPA, Universitas Negeri Padang Parameters observed were root length, crown length, relative water content, and dry weight. The results showed that the root length showed significant results after a two-way ANOVA test which means that there is an influence on root length while the crown length, relative water content, and dry weight did not show significant results.